The contribution of Dennis P. Gordon to the understanding of New Zealand Bryozoa - Smith, Abigail; Bock, Philip; Batson, Peter (New Zealand Science Review, 2016)
​Few biologists have had such an impact on the understanding of New Zealand biodiversity as Dr Dennis Preston Gordon (1944 – ) (Figure 1). His canon of more than 170 scientific publications covers the full gamut of biodiversity studies, ranging from taxonomy and systematics, ecology, evolution and life history, to large-scale syntheses of regional and global patterns, and the higher order of classification of all living organisms. In the 1990s, as project leader of the taxonomy programme at NIWA, Dennis became increasingly involved in tackling the overarching challenges facing biodiversity science1. His work in this area has informed research and environmental management decision-making in New Zealand and elsewhere. He became an advocate for the organisational infrastructure, networks and databases, required to understand and wisely manage the great menagerie of life on Earth. In this capacity he played many key roles at an international level. Dennis chaired the Species 2000 Asia-Oceania Working Group, and served on the Ocean Biogeographic Information System (OBIS) International Committee and on the Steering Committee of WoRMS, the World Register of Marine Species. Dennis Gordon’s magnum opus is the New Zealand Inventory of Biodiversity – a momentous, three-volume work2. Its brief was to inventory all species known to exist – or to have existed – in all of New Zealand’s terrestrial and aquatic environments over the last half billion years. After a decade of sustained scholarship and organisation (the Inventory has 237 authors from 19 countries), it is a resource that the entire nation can take pride in. No other country has produced a similar document. To a different, smaller and more dispersed community, Dennis wears a different hat. He is one of the world’s leading bryozoan biologists and taxonomists. His contribution to under-standing of this phylum in New Zealand and beyond has been immense. This article describes the bryozoological legacy (so far) of Dr Dennis Preston Gordon.